Selection of optimal human myoblasts based on patient related factors influencing proliferation and differentiation capacity - Moritz Englich; Andreas Arkudas; Lilly Mengen; Raymund E. Horch; Aijia Cai (Scientific Reports)
Abstract Human myoblasts (hMb) are a promising source for engineering skeletal muscle tissue. But sample-specific variabilities make research with human cells challenging. For the purpose of selecting hMb with adequate proliferation and differentiation properties, the influence of various patient related factors, including age, gender, BMI, anatomical sampling site and previous radio-/chemotherapy on hMb behavior was investigated in this study. Immunofluorescence staining and proliferation periods were analysed for proliferation capacity, while creatine kinase and cell viability assay, immunofluorescence staining and PCR were used to determine differentiation capacity. Using desmin expression, a multiple linear regression (MLR) model was established based on the above-mentioned patient related factors. Higher age and BMI, female gender and chemotherapy had a negative impact on desmin expression. Muscle type specific differences could also be seen. Previous radiotherapy led to senescence of hMb in large parts. Differentiation was mainly influenced by gender in a time-dependent manner, as well as by the anatomical collecting site. We were able to demonstrate the importance of analyzing patient characteristics for the purpose of hMb isolation. Using MLR, these patient characteristics can be used to predict the proliferation capacity of hMb as a step further towards translational application of skeletal muscle engineering and regeneration.